2012
DOI: 10.5296/jbls.v3i1.2220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substituting Some Components of Broilers’ Feed with Crude Aquous Extract of Fresh Leaves of Mucuna Poggei

Abstract: We studied the effects of substitution of Palm kernel cake (PKC), Fishmeal and Soyabean Cake (SBC) with crude extract of Mucuna poggei on the performances of broilers. A total of forty broiler chicks of a day old each were bought and shared into four groups of ten broilers each, allowed to acclimatize for two weeks and then reared for eight weeks. Palm kernel Cake (PKC), Fishmeal and Soyabean Cake (SBC) were given to broilers in groups 1, 2 and 3 respectively with similar quantities of crude extract of Mucuna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…These show that there is correlation between the live-weights of the birds and the weights of their carcasses as reported by Oko et al, (2012). The low live-weight and low carcasses weight gained by the group C that consumed the highest quantity of sun-dried leaves of Mucuna poggei could be attributed to their higher consumption of antinutrient factors such as phytate, saponin, alkaloids, tanin, L-Dopa, hydrogen cyanide, trypsin inhibitors etc present in the leaves as reported by Oko et al, (2012). Phytate is an anti-nutrient known to increase mineral requirement in animals by forming complexes with minerals.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…These show that there is correlation between the live-weights of the birds and the weights of their carcasses as reported by Oko et al, (2012). The low live-weight and low carcasses weight gained by the group C that consumed the highest quantity of sun-dried leaves of Mucuna poggei could be attributed to their higher consumption of antinutrient factors such as phytate, saponin, alkaloids, tanin, L-Dopa, hydrogen cyanide, trypsin inhibitors etc present in the leaves as reported by Oko et al, (2012). Phytate is an anti-nutrient known to increase mineral requirement in animals by forming complexes with minerals.…”
Section: Discussionsupporting
confidence: 74%
“…Cost of feed is the most important single factor militating against profit-making among poultry farmers in Nigeria. It has been reported that poultry feeds account for about 70-80% of the total cost of poultry production (Olomu, 1979 andOko et al, 2012). According to Afolabi et al, (2005), a great percentage of this feed cost arises from providing adequate energy source in form of grains.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations